1999
DOI: 10.1021/cm990278u
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Structures and Optoelectronic Properties of Oxygen- and Sulfur-Containing Heterocycles:  Conjugated Nonylbisoxazole and Nonylbithiazole Oligomers

Abstract: The synthesis and characterization of 4,4′-dinonyl-2,2′-bisoxazole (NBO) and its oligomers are described. The optical, electronic, and structural properties of these oligomers, NBO, NBO 2 , and NBO 3 , are compared to their sulfur analogues (NBT, NBT 2 , and NBT 3 ). In the series (NBO) n and (NBT) n , there is a red shift in the λ max as "n" increases. This effect is observed in both the solid and solution states. The bithiazole oligomers have longer wavelength absorbances than those of the bisoxazole oligome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 50 publications
2
40
0
Order By: Relevance
“…However, it may also be postulated that chromic phenomena can partly (or even only) reflect temperature‐dependent interchain interactions that accompany the formation (or disruption) of small aggregates or microcrystallites. Recently, many studies have been devoted to the analysis of the relative contribution of chromophore aggregation and planarization on the optical properties of the various chromic conjugated polymers 7–18. Among these studies, a series of analyses on oligothiophene model compounds and polythiophenes have suggested that the chromic effects observed in these organic materials are mainly due to conformational changes 14–17.…”
Section: Introductionmentioning
confidence: 99%
“…However, it may also be postulated that chromic phenomena can partly (or even only) reflect temperature‐dependent interchain interactions that accompany the formation (or disruption) of small aggregates or microcrystallites. Recently, many studies have been devoted to the analysis of the relative contribution of chromophore aggregation and planarization on the optical properties of the various chromic conjugated polymers 7–18. Among these studies, a series of analyses on oligothiophene model compounds and polythiophenes have suggested that the chromic effects observed in these organic materials are mainly due to conformational changes 14–17.…”
Section: Introductionmentioning
confidence: 99%
“…In the inverse process (formation of planar assemblies), the chromic behavior is probably the result of assisted planarization in which interchain interactions stacking forces the polymer chains into a more rigid conformation. 46,54 However, it was also postulated that thermochromic changes may reflect some interchain interactions (excitons, p-p stacking) that accompany the formation of small aggregates (this is obvious in the solid state) or microcrystallites. 46 Planarization always leads to a red shift, but the direction of the shift caused by aggregation depends on the details of the molecular packing in the solid state.…”
Section: Biographical Sketchesmentioning
confidence: 99%
“…46,54 However, it was also postulated that thermochromic changes may reflect some interchain interactions (excitons, p-p stacking) that accompany the formation of small aggregates (this is obvious in the solid state) or microcrystallites. 46 Planarization always leads to a red shift, but the direction of the shift caused by aggregation depends on the details of the molecular packing in the solid state. Further studies will be required to determine the relative contribution of chromophore aggregation and planarization on the optical properties of various chromic conjugated polymers.…”
Section: Biographical Sketchesmentioning
confidence: 99%
See 1 more Smart Citation
“…[1] Aggregates of conjugated polymers such as poly(paraphenylene-vinylene)s, [2] poly(paraphenylene-ethynylene)s (PPE), [3] or polythiophenes [4] have significantly different physical, optical, and electronic properties from those of single molecules of these polymers. Aggregation of conjugated polymers is (potentially) relevant to device technology [5a, b] and molecular electronics, [5b] but is likewise of fundamental interest.…”
Section: Introductionmentioning
confidence: 99%